Evaluation of application methods and biocontrol efficacy of paenibacillus alvei strain K-165, against the cotton black root rot pathogen thielaviopsis basicola - Schoina, Chariklia; Stringlis, Ioannis A.; Tjamos, Sotirios; Paplomatas, Epaminondas J.; Pantelides, Iakovos S. (My University, 2011)
Due to limited means for control, the black root rot fungus, Thielaviopsis basicola constitutes a major threat to organic and conventional cotton production worldwide. Despite the substantial yield loss and reduced fiber quality caused by the fungus, little attention has been drawn to the biological control of black root rot disease. In the present study, the efficacy of the biocontrol agent K-165 to control T. basicola on cotton was evaluated. Paenibacillus alvei strain K-165 is a biocontrol agent that has been studied extensively in the past against the soilborne pathogen Verticillium dahliae. K-165 inhibited T. basicola growth in vitro through antibiosis and reduced significantly root discoloration and hypocotyl lesions on cotton seedlings compared to the control treatment, under greenhouse conditions. In the in planta experiments three different application methods of the biocontrol agent were tested. It was shown that a seed coating treatment consisting of K-165 xanthan gum and talc was the most effective in reducing disease symptoms and increasing plant height and fresh weight compared to two other treatments (seed coating or pellets) based on sodium alginate. The efficacy of the K-165 xanthan gum-talc treatment was attributed to the higher bacterial concentration delivered to the seed and the subsequent higher bacterial population on the rhizosphere and soil compared to the other two application methods. K-165 was proven to be an efficient root and soil colonizer inhibiting extensive root colonization by T. basicola as it was shown by qPCR analysis
Keywords: Biological control; Gossypium hirsutum L.; Pellets; Seed coating; Sodium alginate